Physicochemical Properties of Goat Milk Dodol Fortified with Eucheuma spinosum Seaweed - Andari, Dyana Kusuma; Sujarwo, Rama Aben; Rahayu, Premy Puspitawati; Zul’adhar, Ulya Rafa (CV. Komunitas Dunia Peternakan, 2025)
This study aimed to evaluate the effect of adding Eucheuma spinosum seaweed on the quality of goat milk dodol on moisture, protein, fat, and color (L*, a*, b*). Goat milk was chosen due to its high nutritional value and better digestibility than cow milk, although its consumption in Indonesia remains limited because of its strong odor, while dodol, a traditional Indonesian confection with a chewy texture, was used as a base product to promote milk utilization. The research material was dodol made from goat milk, glutinous rice flour, sugar, and salt, with the addition of Eucheuma spinosum seaweed at concentrations of 0% (T0), 10% (T1), 20% (T2), and 30% (T3). The method used was a laboratory experiment employing a Completely Randomized Design (CRD) with four treatments and five replications. The obtained data were then analyzed using analysis of variance (ANOVA). If significant differences were found, the Duncan Multiple Range Test (DMRT) was conducted. The results showed a protein content value of 5.33%-6.37%. Fat content value of 11.96%-13.19%. Ash content value ranged from 1.49%-3.96%. Texture value ranged from 16.22 N-26.44 N. pH value ranged from 6.76-6.94. Color parameter value L* ranged from 39.65-45.39; a* 5.16-8.33; b* 21.16-22.71. Organoleptic value of texture 2.50-3.48; color 2.08-3.79; aroma 3.69-3.83; taste 3.02-3.47.